DERADICALISATION: BETWEEN THEORY AND PRACTICE - DUȚU, Daniel-Mihai (Strategic Impact, 2022)
To combat extremist ideologies and the threat of mass radicalisation, experts have developed a series of research in order to identify and understand the factors that lead to the radicalisation of an individual, but also the factors that, having an opposite effect, can lead to its deradicalisation. Therefore, more and more authors recognize the importance of studying the process of deradicalisation and its potential for today’s society. Hence, the paper aims to further address this process by presenting specific terminology, theoretical and practical models of deradicalisation, and signalling difficulties and limitations during the development of national disengagement and deradicalisation programs caused by the lack of practical information on the results of these initiatives.